Cellular and Molecular Defects Underlying Invasive Fungal Infections—Revelations from Endemic Mycoses - Lee, Pamela P.; Lau, Yu-Lung (Frontiers in Immunology, 2017)
The global burden of fungal diseases has been increasing, as a result of the expanding number of susceptible individuals including people living with human immunodeficiency virus (HIV), hematopoietic stem cell or organ transplant recipients, patients with malignancies or immunological conditions receiving immunosuppressive treatment, premature neonates and the elderly. Opportunistic fungal pathogens such as Aspergillus, Candida, Cryptococcus, Rhizopus and Pneumocystis jiroveci are distributed worldwide and constitute the majority of invasive fungal infections (IFI). Dimorphic fungi such as Histoplasma capsulatum, Coccidioides spp., Paracoccidioides spp., Blastomyces dermatiditis, Sporothrix schenckii, Talaromyces (Penicillium) marneffei and Emmonsia spp. are geographically restricted to their respective habitats and cause endemic mycoses. Disseminated histoplasmosis, coccidioidomycosis and T. marneffei infection are recognized as AIDS-defining conditions, while the rest also cause high rate of morbidities and mortalities in patients with HIV infection and other immunocompromised conditions. In the past decade, a growing number of monogenic immunodeficiency disorders causing increased susceptibility to fungal infections have been discovered. In particular, defects of the IL-12/IFN-gamma pathway and T-helper 17-mediated response are associated with increased susceptibility to endemic mycoses. In this review, we put together the various forms of endemic mycoses on the map and take a journey around the world to examine how cellular and molecular defects of the immune system predispose to invasive endemic fungal infections, including primary immunodeficiencies, individuals with autoantibodies against interferon-gamma, and those receiving biologic response modifiers. Though rare, these conditions provide importance insights to host defense mechanisms against endemic fungi, which can only be appreciated in unique climatic and geographical regions.